Transfer of Property of the Deceased to the Ownership of Public Legal Entities - BORYSLAVSKA, Maryna (University Scientific Notes, 2020)
Public law entities such as the state and the territorial community have been found to have general grounds for acquiring ownership of property left after the death of an individual in the following cases: they are indicated in the will as an heir; the heir waives the share due to him/her in favor of the state or territorial community. In addition, each of these entities has grounds for acquiring (inheriting) the property of the deceased, relating exclusively to him-her. Thus, a territorial community becomes the successor of the property of the deceased person, in respect of whom there were no heirs after being recognized by court as fictitious in the manner prescribed by law. The property of the deceased may pass to the state in two other cases: the inheritance was opened before July 1, 2003, but was not accepted by any of the heirs (according to article 555 of the Civil Code of Ukraine of 1963); The state of Ukraine is the heir to international treaties. It is established that the latter ground is not mentioned in the Civil Code of Ukraine, which is assessed as a gap in legislation. A detailed analysis of all the mentioned grounds for the acquisition of property of the deceased is carried out. The conclusion is confirmed that the transition to a territorial community of fizzy inheritance is not inheritance. The possibility of submitting an application to the court for recognition of the inheritance as a fictitious body of the prosecutor’s office in the interests of the territorial community, which usually occurs with the inaction of the local government, is justified. The following features of the recognition of inheritance as a fictitious property are highlighted: 1) the rules of law that fix the transition of the hereditary mass to the favor of the territorial community are mandatory in nature, that is, the local government body in its interests is obliged to apply to the court; 2) only one participant in civil legal relations — the territorial community acquires property that has not been inherited; 3) there is no limitation (maximum period) on the moment for appeal to the court; 4) to recognize the inheritance as fictitious, a person needs an appropriate court decision that has entered into legal force. It is proposed to supplement the Civil Code of Ukraine with article 12771 on the transfer to the state of inheritance discovered abroad.
Keywords: public legal entities; state; territorial community; inheritance; property of the deceased; recognition of inheritance as fictitious